2015
DOI: 10.1186/2045-3701-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanog down-regulates the Wnt signaling pathway via β-catenin phosphorylation during epidermal stem cell proliferation and differentiation

Abstract: BackgroundSkin tissue homeostasis is maintained by a balance between the proliferation and differentiation of epidermal stem cells (EpSCs). EpSC proliferation and differentiation are complex processes regulated by many factors and signaling pathways. This study aimed to explore the connection between the Nanog and the Wnt/β-catenin pathway in the proliferation and differentiation of EpSCs.ResultsOur results demonstrated that during the study period, EpSC underwent differentiation when incubated in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Following treatment for 48 h, the expression of MYC was significantly decreased by Rau treatment, which is consistent with Wnt/β-catenin signaling pathway inhibition. Studies have shown that the stem cell-related gene Nanog has the ability to induce β-catenin phosphorylation and enhances its degradation ( 38 ). Therefore, the present study examined the expression of Nanog by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Following treatment for 48 h, the expression of MYC was significantly decreased by Rau treatment, which is consistent with Wnt/β-catenin signaling pathway inhibition. Studies have shown that the stem cell-related gene Nanog has the ability to induce β-catenin phosphorylation and enhances its degradation ( 38 ). Therefore, the present study examined the expression of Nanog by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that a stem cell related gene Nanog can induce β-catenin phosphorylation and therefore enhance its degradation, and consequently inhibit Wnt signaling pathway. 35 We therefore examined the expression of Nanog by Western blot. Nanog was increased at 24 hours of Pao treatment but was decreased at 48 hours of Pao treatment ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our study shows how constitutive heterozygous germline mutations affect early kidney development and provides further insights into the mechanisms underlying the renal developmental abnormalities associated with RCAD and their consequences in postnatal life. In summary, the Hnf1b Sp2/+ mouse model represents a unique clinical/pathological viable model of the human disease and promises to be important in the integrative evaluation, in the context of the whole animal, of the broad facets of this disease, ranging from various developmental abnormalities to kidney, pancreas and liver dysfunctions as well as tumorigenesis ( Yu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%